Development of E-Government Innovation at the Urban Level: A Systematic Literature Review - Suprianto, Suprianto (Journal of Public Policy and Local Government (JPPLG), 2025)
This study applies the Systematic Literature Review (SLR) approach to comprehensively explore the models, strategies, and factors that affect the successful implementation of e-government innovation at the city level. This approach was chosen to provide a structured and objective scientific synthesis of previous research results while mapping the development of knowledge and identifying research gaps. The literature review process follows the PRISMA protocol, encompassing the stages of identification, screening, eligibility, and inclusion, with a focus on Scopus-indexed articles published between 2021 and 2025 related to digital innovation, innovative city governance, and public service transformation. The analysis was conducted using a thematic analysis method to categorize findings based on key themes, including digital technology, organizational readiness, citizen participation, leadership, and regulations. The study's results demonstrate that e-government has excellent transformative potential in enhancing the efficiency of public services, strengthening transparency, and increasing citizen participation. The success of implementation is heavily influenced by the leadership role and organizational culture that supports innovation. However, challenges such as the digital divide, scalability, and contextual differences between cities remain obstacles that need to be overcome. This study highlights the significance of contextual approaches and community engagement in the development of inclusive and sustainable e-government. Thus, this research contributes to the development of conceptual mapping and recommendations for policy directions that support the effective and accountable digital transformation of urban governance.